The state of costing research for HIV interventions in sub-Saharan Africa. Issue 4 (6th December 2019) - Cameron, Drew B; Mustafa Diab, Mohamed; Carroll, Lauren N; Bollinger, Lori A; DeCormier Plosky, Willyanne; Levin, Carol; Herzel, Benjamin; Marseille, Elliot; Alexander, Lily; Bautista-Arredondo, Sergio; Pineda-Antunez, Carlos; Cerecero-García, Diego; et al.
Abstract : The past decade has seen a growing emphasis on the production of high-quality costing data to improve the efficiency and cost-effectiveness of global health interventions. The need for such data is especially important for decision making and priority setting across HIV services from prevention and testing to treatment and care. To help address this critical need, the Global Health Cost Consortium was created in 2016, in part to conduct a systematic search and screening of the costing literature for HIV and TB interventions in low- and middle-income countries (LMIC). The purpose of this portion of the remit was to compile, standardise, and make publicly available published cost data (peer-reviewed and gray) for public use. We limit our analysis to a review of the quantity and characteristics of published cost data from HIV interventions in sub-Saharan Africa. First, we document the production of cost data over 25 years, including density over time, geography, publication venue, authorship and type of intervention. Second, we explore key methods and reporting for characteristics including urbanicity, platform type, ownership and scale. Although the volume of HIV costing data has increased substantially on the continent, cost reporting is lacking across several dimensions. We find a dearth of cost estimates from HIV interventions in west Africa, as well as inconsistent reporting of key dimensions of cost including platform type, ownership and urbanicity. Further, we find clear evidence of a need for renewed focus on the consistent reporting of scale by authors of costing and cost-effectiveness analyses.